A high‐energy‐resolution resonant inelastic X‐ray scattering spectrometer at ID20 of the European Synchrotron Radiation Facility. (20th February 2018) - Moretti Sala, M.; Martel, K.; Henriquet, C.; Al Zein, A.; Simonelli, L.; Sahle, Ch. J.; Gonzalez, H.; Lagier, M.-C.; Ponchut, C.; Huotari, S.; Verbeni, R.; Krisch, M.; et al.
Abstract : An end‐station for resonant inelastic X‐ray scattering at beamline ID20 of ESRF – The European Synchrotron is described. The spectrometer is optimized for high‐energy‐resolution applications, including partial fluorescence yield or high‐energy‐resolution fluorescence detected X‐ray absorption spectroscopy and the study of elementary electronic excitations in solids. Abstract : An end‐station for resonant inelastic X‐ray scattering and (resonant) X‐ray emission spectroscopy at beamline ID20 of ESRF – The European Synchrotron is presented. The spectrometer hosts five crystal analysers in Rowland geometry for large solid angle collection and is mounted on a rotatable arm for scattering in both the horizontal and vertical planes. The spectrometer is optimized for high‐energy‐resolution applications, including partial fluorescence yield or high‐energy‐resolution fluorescence detected X‐ray absorption spectroscopy and the study of elementary electronic excitations in solids. In addition, it can be used for non‐resonant inelastic X‐ray scattering measurements of valence electron excitations.